Ticari banka değerleme: Türkiye örneği - Kalfa, Mehmet Ali (My University, 2001)
The word 'bank' is thought to stem from an italian word 'banco'. This word means table, desk, line or workbench. It has been found by archaeological digs that the first time in the world the banking activities had been done by the Anotolien civilizations approximately about 3500 B.C. With the Renissance movements banking activities had got a new dimension. While the geographical discoveries and the beginnings of industrialization the first banks had been settling down. Because the Ottomans could not follow the Europeans, the beginning of banking activities had been postponed until the mid 19th century. Before being announced of the Republic of Turkey there had been foreing banks settled down in Ottomans' boundary and also had been branches of outside headquartered banks. In the beginnings of the Republic a lot of banks have been settled down for the sake of promoting production inland and developing the economy. After 1980's banking in Turkey has started to change it's old shell. But today banking sector in Turkey still faces with big problems. Today it is expected that banking sector will have been rebuilt in the following 6 years. When it is questioned what the scale of a commercial bank is, economic power of a commercial bank, the volume of the activities, equity, number of people working etc. are understood. How different techniques commercial banks use in their activities shows some differences related to banks' scale. For example, small and medium sized banks have some advantages and also some disadvantages depending on their scale. That is why these banks have to think about what sort of clients to work with, credit policies, optimum liquidity requirements etc. Although retail banking is also done by small and medium sized commercial banks this business is the real business of large sized commercial banks because retail banking requires branches everywhere where are potential cleints. As depending on the scale large sized commercial banks prefer wholesale banking. Wholesale banking is to get a tight relations with clients and to operate with large amounts of money. Also all commercial banks can found offshore banks to get some barriers for the countries' law. Commercial banks' activities can also include investment banking activities. Investment banking is to consult to the people who has big amount of capital. For a good valuation of a commercial bank, what does refer to a commercial bank's balance sheet and an income statement are to be known. Asset side of the balance sheet shows that where the banks resources are used or where unused ones are. In the liabilities side of balance sheet it is showed that from where the bank has found the resources i.e. to which people bank has responsibilities. In this sense, grouping of the asset side and the liabilities side of the balance sheet in different categories help the analysists understand commercial banks' financial structure. Income statement points out revenues and to get these revenues what bank has made as expenditures. Working on income statement and also grouping the items give clearer informations about the bank under valuation. As all firms, a commercial bank tries to maximize its profit. To do this, bank tries to have a good liquidity to show bank's power one side. On the other side, a bank has to increase risk by using nearly all liquidity to maximize profit. In other words, managing the balance sheet stands for managing the risk and the liquidity. Risk management is the management of probability of being met of unwanted events. For the managers of a commercial bank risks come from two sources. One of them is financial originated the other is service originated. Financial risk can be subdivided into 5 categories. These are namely liquidity risk, credit risk, foreign exchange risk, risk coming from participations and from other related firms and risk borned by bank's internal activities. Service risk, however, can be subdivided into 3 categories. These are namely operating risk under maximum efficiency, risk coming from unexpected official law regulations that can make the firms' profitability down and the risk coming from technological improvement i.e. when technology changed the one bank uses gets old that reduces profitibility. In addition to these risk definitions, there can also be different types of risk definitions from the perspectives of depositors and managers of the bank. As is focused on liquidity management in commercial banks there are two main approaches. The first is asset approach in the need for liquidity. In this approach, when liquidity is needed assets is used to find the liquidity. In other words, banks in this aspect hold the line of maximum revenue from loans and securities and minimum risk so bank has always enough liquidity in hand. The second approach is liabilities approach. In this approach, dimension of the items in the liability side is cared with and when needed how fast these items are resolved is detected. A commercial bank follow credit policies parallel with the directions of the top managers of bank. In Turkey these policies must be in line with Banking Law and Turkish Trade Law. In these policies how amount, in which terms and conditions and to whom credits can be given is conditioned. How a commercial bank finds the funds it needs to make loans is also an important aspect for valuation. In general sense, commercial banks finds the funds from depositors for a period less than 1 year, from international financial institutions as long term credit and from the people who has already supplied bank's capital. These resources can then be extended to people who needs credit, to investment funds and to investment to securities, to participations, to treasury bills and government and private sector bonds and to real estate. There are some ratios that help valuations and make valuations easy. These ratios are sometimes calculated directly from the balance sheet data and at other times additional data is required. The most phosphoreous ratio is current ratio in liquıdity ratios. Calculating current ratio for commercial banks is a problematic task. Normally current ratio is a ratio of current assets over current liabilities. The word 'current' stands for 1 year perid of time. This ratio does not operate good for commercial banks in Turkey. Other than current ratio, there are some other liquidity ratios. These are namely net working capital over total assets, interval ratio, current ratio for a very much period of time and financial expendiures turnover ratio. Total debt ratio, debt / equity ratio, shareholder's equity multiplier, long term debt ratio, cash requirements ratio, shareholder's equity share and long term shareholder's equity share are a commercial banks long term liquidity ratios. Return on assets, return on equity are the main profitibility ratios. While making a commercial bank valuation calculating also price earning ratio, market value / book value and Tobins' q give the analysists some additional perspectives. Finally at valuations the standing criterions can also be used to understand a commercial bank's financial structure. Mains of the standing criterions are return on equity, equity borrowed ratio, credits over equity and leverage ratio. The calculations of assets size, book value and net current year profit show that the value of Dışbank A.Ş. is in the interval of 250 millions of dollars and ile 392 millions of dollars. Here is used a multiplier calculated from the last balance sheet data and closing prices to see how the final developments in financial markets affect the valuation. Although net current year profit is also used to value a bank in Turkey this does not give a right sense because commercial banks in Turkey get enormous amount of profits by buying government papers. In this sense, valuations by net current year profit were here not taken into consideration. Because there are alerted financial markets for political and economical developments, last year multipliers are very much differentiated from average multipliers for the commercial bank under valuation. This situation can be checked out to understand whether the situations are the same for other commercial banks. Then it can be said that this is because of the bank's performance or in this scale all banks show the same performances. Commercial bank valuation can also be done with the multiplier by taken a selected peer group into consideration. So final year average or last years' avarage have been used in the calculation of new multipliers. In this line, the new valuations are found between 116 millions of dollars and 184 millions of dollars, 216 millions of dollars 425 millions of dollars respectively. Another approach in valuation is current cash flow analysis. In this technique some adjustments are made on net interest income and then cash flow from operating activities is reached. The next step is to find the market value. Then the market value over current cash flow is compared with ratios calculated for other banks and so a final decesion is reached whether the bank in valuation is expensive or cheap in market. In this sense, calculated ratio for Dışbank A.Ş. 2.41 that is operating cash flow multiplier. With this work for many aspects of interest how a bank valuation is done has been searched. It has been reached that to value a bank is not an easy task because there are lots of complications. However, a bank could have been valued in an interval. A commercial bank can then be priced between this interval with the help of other financial evaluations explained above.
Keywords: Banka ve bankacılık; BANKALAR VE BANKACILIK-TÜRKİYE; Ekonomi; Finansman ekonomisi; Ticari bankalar (Takas bank)